A high bonding force molybdenum disulfide-based composite self-lubricating coating for a transmission fork and a dip coating method thereof
Patent Information
- Application Number
- CN202610964691.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-20
AI Technical Summary
但其涂覆技术仍存在涂层结合力不足的问题
本发明用于传动拨叉的高结合力二硫化钼基复合自润滑涂层的浸涂方法中,先按1.0:(1.0~3.0)的质量比混合硅藻土与粘结剂制成浆料,经1~3次浸涂形成厚度10~18μm的多孔中间层,再将超声分散后的二硫化钼涂料浸涂8~15μm润滑面层,分步固化抛光得到复合涂层,整套分层浸涂结构能够针对性解决现有直接涂覆二硫化钼涂层附着力差、润滑相分布不均、磨损严重的问题,具体的:首先,经实验,本发明在该限定配比下的硅藻土中间层可保留完整多孔骨架,一方面孔隙结构能和拨叉基体、上层润滑涂层形成双向机械嵌合锚固,增大界面接触面积,缓解基体与涂层间力学、热学性能差异带来的界面应力;若硅藻土占比过高,粘结剂不足以包裹颗粒会造成中间层松散,粘结剂过量又会填满孔隙丧失咬合结构,本发明的配比区间刚好兼顾骨架完整性与结构牢固度,从结构层面避免涂层长期摩擦起皮脱落。其次,分步浸涂的结构搭配超声分散处理的二硫化钼涂料,能让润滑颗粒渗入硅藻土孔隙内部,依靠多孔骨架对二硫化钼起到分隔限域作用,抑制润滑相团聚沉降,摩擦过程中孔隙内储存的润滑介质可持续向接触面补给,稳定维持润滑膜;经试验,本发明技术方案制备的涂层摩擦系数与磨损率均能控制较更低水平,有效降低拨叉往复运动过程的磨损损耗,延长工件使用寿命。同时本发明技术方案分别限定中间层、润滑面层的浸涂厚度,较厚的多孔中间层提供充足锚固位点,薄而均匀的二硫化钼面层直接承担摩擦作用,两层分开浸涂、分开固化也能规避单次厚涂带来的溶剂挥发不均、涂层开裂气泡等缺陷,即便缩短浸渍时间、减少涂料附着量,涂层摩擦与磨损性能也仅刚好达到性能上限,足以说明分层厚度与分步浸涂工艺是稳定实现低摩擦、高耐磨性能的必要条件。另外全程采用浸渍成型工艺,无需特殊高端涂覆设备,原料硅藻土易得、固化温度温和,不会损伤拨叉基体材料,工序简洁易批量加工,在保证涂层使用性能的同时降低生产门槛与制造成本,能够适配航空传动拨叉的批量涂覆需求。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lubrication technology, specifically a high-bonding-strength molybdenum disulfide-based composite self-lubricating coating for transmission shift forks and its dipping method. Background Technology
[0002] The transmission fork is a key component in pneumatic-hydraulic actuators. It utilizes gas pressure to drive a piston, which then converts linear motion into rotational motion via the fork, thereby opening and closing valves. In the aerospace field, transmission forks in pneumatic-hydraulic actuators are commonly used in aircraft landing gear systems and flight control systems. Because the transmission fork generates significant friction during reciprocating or rotating motion, it is prone to component wear, shortening its service life. MoS2-based composite self-lubricating materials, due to their low coefficient of friction and excellent chemical stability, have been widely used in the field of self-lubricating coatings for pneumatic-hydraulic actuator transmission forks. However, their coating technology still suffers from insufficient coating adhesion. Therefore, the development of a novel high-adhesion molybdenum disulfide-based composite self-lubricating coating and its dip-coating method is urgently needed. Summary of the Invention
[0003] To address the problems existing in the prior art, the present invention aims to provide a high-bonding molybdenum disulfide-based composite self-lubricating coating for transmission shift forks and its dipping method. The present invention can improve the bonding force between the coating and the substrate.
[0004] To achieve the above objectives, the present invention provides the following technical solution: A dip-coating method for a high-adhesion molybdenum disulfide-based composite self-lubricating coating for a transmission shift fork includes the following steps: S1. Mix diatomaceous earth powder and binder evenly at a mass ratio of 1.0:(1.0~3.0) to obtain a mixed slurry; S2. Apply the mixed slurry evenly to the substrate surface using an impregnation method. The thickness of each application is 10-18 μm, and the application is repeated 1-3 times. After that, the substrate is dried and cured to obtain a substrate with diatomaceous earth attached. S3. The molybdenum disulfide-based composite coating is uniformly dispersed by ultrasonication, and then uniformly coated onto the substrate with diatomaceous earth by impregnation. The coating thickness is 8-15 μm. After coating, the coating is dried and cured, and finally polished to obtain a molybdenum disulfide-based composite self-lubricating coating.
[0005] Preferably, the adhesive is at least one selected from silica sol, epoxy resin, phenolic resin, and vinyl resin.
[0006] Preferably, in step S2, the drying and curing temperature is 30–70°C, and the drying and curing time is 2–8 hours.
[0007] Preferably, in step S3, the molybdenum disulfide-based composite coating is ultrasonically dispersed until it reaches a non-Newtonian high-viscosity fluid state.
[0008] Preferably, in step S3, the ultrasonic temperature is 35–70°C and the ultrasonic time is 15–110 min.
[0009] Preferably, in step S3, the drying and curing temperature is 45–80°C, and the drying and curing time is 3–10 hours.
[0010] Preferably, the molybdenum disulfide-based composite coating comprises: molybdenum disulfide, PEEK, and Ti3C2Tx powder; wherein the mass ratio of molybdenum disulfide, PEEK, and Ti3C2Tx powder is 1.0:(0.5-1.2):(0.1-0.6). Alternatively, the components of the molybdenum disulfide-based composite coating include: molybdenum disulfide, PEEK, and PFA; wherein the mass ratio of molybdenum disulfide, PEEK, and PFA is 1.0:(0.3-1.0):(0.2-1.2). Alternatively, the components of the molybdenum disulfide-based composite coating include: molybdenum disulfide, black phosphorus powder, alumina powder, and titanium dioxide powder; wherein the mass ratio of molybdenum disulfide, black phosphorus powder, alumina powder, and titanium dioxide powder is 1.0:(0.1-0.4):(0.1-0.8):(0.1-0.5).
[0011] Preferably, in step S2, the immersion time for a single immersion is 10 to 15 minutes; in step S3, the immersion time is 15 to 20 minutes.
[0012] The present invention also provides a high-adhesion molybdenum disulfide-based composite self-lubricating coating for a transmission shift fork, which is prepared by the dip-coating method of the present invention described above.
[0013] Preferably, the high-adhesion molybdenum disulfide-based composite self-lubricating coating for the transmission shift fork has a friction coefficient ≤0.242 and a wear rate ≤3.15% under the conditions of a load of 0.95-1.05N, a frequency of 45-50Hz, and a test time of 18-22min.
[0014] The present invention has the following beneficial effects: In the dip-coating method of the high-adhesion molybdenum disulfide-based composite self-lubricating coating for transmission shift forks of the present invention, diatomaceous earth and binder are first mixed at a mass ratio of 1.0:(1.0~3.0) to prepare a slurry. This slurry is then dip-coated 1~3 times to form a porous intermediate layer with a thickness of 10~18μm. Next, an ultrasonically dispersed molybdenum disulfide coating is dip-coated into an 8~15μm lubricating surface layer. Stepwise curing and polishing are then performed to obtain the composite coating. This layered dip-coating structure specifically addresses the problems of poor adhesion, uneven distribution of the lubricating phase, and severe wear associated with existing directly coated molybdenum disulfide coatings. Specifically: Firstly... Experiments have shown that the diatomaceous earth intermediate layer of this invention, under the specified ratio, can retain a complete porous framework. On the one hand, the pore structure can form a two-way mechanical interlocking and anchoring with the fork substrate and the upper lubricating coating, increasing the interface contact area and alleviating the interface stress caused by the difference in mechanical and thermal properties between the substrate and the coating. If the proportion of diatomaceous earth is too high, the binder will not be enough to wrap the particles, causing the intermediate layer to become loose. If the binder is too much, it will fill the pores and lose the interlocking structure. The ratio range of this invention just takes into account both the integrity of the framework and the structural firmness, thus avoiding long-term friction peeling and detachment of the coating from a structural perspective. Secondly, the step-by-step dip coating structure, combined with the ultrasonically dispersed molybdenum disulfide coating, allows the lubricating particles to penetrate into the pores of the diatomaceous earth. The porous framework plays a role in separating and confining the molybdenum disulfide, inhibiting the agglomeration and sedimentation of the lubricating phase. During the friction process, the lubricating medium stored in the pores can be continuously replenished to the contact surface, stabilizing the lubricating film. Experiments have shown that the coating prepared by the technical solution of this invention can control the coefficient of friction and wear rate to a lower level, effectively reducing the wear loss during the reciprocating motion of the fork and extending the service life of the workpiece. Meanwhile, the technical solution of this invention limits the coating thickness of the intermediate layer and the lubricating surface layer respectively. The thicker porous intermediate layer provides sufficient anchoring points, while the thin and uniform molybdenum disulfide surface layer directly bears the frictional action. The separate dipping and curing of the two layers can also avoid defects such as uneven solvent evaporation, coating cracking and blistering caused by single thick coating. Even if the immersion time is shortened and the amount of coating adhesion is reduced, the friction and wear performance of the coating only just reaches the upper limit of performance, which is enough to show that the layer thickness and the step-by-step immersion coating process are necessary conditions for stably achieving low friction and high wear resistance. In addition, the entire process adopts the immersion molding process, which does not require special high-end coating equipment. The raw material diatomaceous earth is readily available and the curing temperature is mild, which will not damage the shift fork substrate material. The process is simple and easy to mass-produce. While ensuring the performance of the coating, it reduces the production threshold and manufacturing cost, and can meet the mass coating needs of aerospace transmission shift forks. Attached Figure Description
[0015] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0016] Figure 1 The graph shows the friction and wear test curves of the high-bonding molybdenum disulfide-based composite self-lubricating coating used for transmission forks, obtained in Example 1.
[0017] Figure 2 The graph shows the friction and wear test curves of the high-bonding molybdenum disulfide-based composite self-lubricating coating used for the transmission fork obtained in Example 2.
[0018] Figure 3 The graph shows the friction and wear test curves of the high-bonding molybdenum disulfide-based composite self-lubricating coating used for the transmission fork obtained in Example 3.
[0019] Figure 4 The graph shows the friction and wear test curves of the high-bonding molybdenum disulfide-based composite self-lubricating coating used for the transmission fork obtained in Example 4.
[0020] Figure 5 The graph shows the friction and wear test curves of the high-bonding molybdenum disulfide-based composite self-lubricating coating used for the transmission fork obtained in Example 5.
[0021] Figure 6 The graph shows the friction and wear test curves of the coating obtained in Comparative Example 1.
[0022] Figure 7 The graph shows the friction and wear test curves of the coating obtained in Comparative Example 2.
[0023] Figure 8 The graph shows the friction and wear test curves of the coating obtained in Comparative Example 3. Detailed Implementation
[0024] The technical solutions described below in conjunction with the embodiments will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] This invention proposes a high-bonding molybdenum disulfide-based composite self-lubricating coating for transmission shift forks and its dipping method. By introducing diatomaceous earth to construct a porous framework intermediate layer, its porous microstructure forms a strong mechanical bond and anchoring effect with the substrate and the upper lubricating coating, improving interfacial bonding strength and alleviating stress mismatch between the coating and the substrate. This effectively solves the problems of weak bonding and easy detachment when directly coating MoS2. Simultaneously, the porous framework can uniformly bear and disperse the MoS2 lubricating phase, preventing agglomeration, sedimentation, or uneven distribution, ensuring a stable supply of lubricating phase at the friction interface. This achieves a synergistic improvement in low friction coefficient and high wear resistance, meeting the coating requirements of self-lubricating coatings for transmission shift forks in aircraft pneumatic-hydraulic actuators.
[0026] Specifically, the dip-coating method of the present invention for a high-adhesion molybdenum disulfide-based composite self-lubricating coating for a transmission shift fork includes the following steps: S1. The diatomaceous earth powder is mixed with a binder to obtain a mixed slurry; wherein the binder can be at least one selected from silica sol, epoxy resin, phenolic resin, and vinyl resin. Too much diatomaceous earth will result in a loose coating due to insufficient binder, while too much binder will form an excessively thick adhesive layer, affecting the lubrication effect. Therefore, the mass ratio of diatomaceous earth to binder in this invention is 1.0:(1.0~3.0). Specifically, the mass ratio of diatomaceous earth to binder can be any one of 1.0:1.0, 1.0:1.5, 1.0:2.0, 1.0:2.5, 1.0:3.0, or any range between two of these.
[0027] S2. Apply the mixed slurry evenly to the surface of the substrate (such as a shift fork) using an impregnation method. The thickness of each application is 10–18 μm, and 1–3 applications are made. Then, dry and cure to obtain a shift fork coated with diatomaceous earth. The single impregnation time is 10–15 min; specifically, the single impregnation time can be any one or any two of 10 min, 11 min, 12 min, 13 min, 14 min, and 15 min. The drying and curing temperature is 30–70℃, and the drying and curing time is 2–8 h; specifically, the drying and curing temperature can be any one or any two of 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, and 70℃; the drying and curing time can be any one or any two of 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, and 8 h.
[0028] S3. Place the molybdenum disulfide-based composite coating in an ultrasonic cleaner and ultrasonically disperse it evenly. Then, use an immersion method to evenly coat the molybdenum disulfide-based composite coating onto the transmission fork with diatomaceous earth attached, with a coating thickness of 8-15 μm. After coating, dry and cure, and finally polish to obtain a molybdenum disulfide-based composite self-lubricating coating. The molybdenum disulfide-based composite coating can be one of the following: specifically, the components of the molybdenum disulfide-based composite coating include: molybdenum disulfide, PEEK (polyetheretherketone), and Ti3C2Tx (titanium carbide MXene) powder; wherein the mass ratio of molybdenum disulfide, PEEK, and Ti3C2Tx powder is 1.0:(0.5-1.2):(0.1-0.6). Alternatively, the molybdenum disulfide-based composite coating may comprise: molybdenum disulfide, PEEK, and PFA (perfluoroalkoxy alkane); wherein the mass ratio of molybdenum disulfide, PEEK, and PFA is 1.0:(0.3–1.0):(0.2–1.2). Alternatively, the molybdenum disulfide-based composite coating may comprise: molybdenum disulfide, black phosphorus powder, alumina powder, and titanium dioxide powder; wherein the mass ratio of molybdenum disulfide, black phosphorus powder, alumina powder, and titanium dioxide powder is 1.0:(0.1–0.4):(0.1–0.8):(0.1–0.5).
[0029] The ultrasonically treated coating reaches a non-Newtonian high-viscosity fluid state. To achieve this state, experiments were conducted, and the ultrasonic temperature was set at 35–70°C, and the ultrasonic time at 15–110 min. Specifically, the ultrasonic temperature can be any one or any two of the following: 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, and 70°C. The ultrasonic time can be any one or any two of the following: 15 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, and 110 min. The impregnation time is 15–20 min; specifically, the impregnation time can be any one or any two of the following: 15 min, 16 min, 17 min, 18 min, 19 min, and 20 min. The drying and curing temperature is 45–80℃, and the drying and curing time is 3–10 hours. Specifically, the drying and curing temperature can be any one or any two of 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, and 80℃. The drying and curing time can be any one or any two of 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, and 10 hours.
[0030] The above-described solution of this invention enables high-efficiency, low-cost, and large-scale coating of molybdenum disulfide-based composite materials for transmission shift forks. In particular, the technical approach of introducing diatomaceous earth to construct a porous skeleton intermediate layer achieves excellent coating results. Simultaneously, this invention also pioneers a novel "matrix-porous skeleton intermediate layer-lubricant layer" coating structure for self-lubrication of friction pair interfaces, demonstrating promising practical applications.
[0031] The technical solution of the present invention will be further described below with reference to specific embodiments.
[0032] Example 1 The dip-coating method for the high-adhesion molybdenum disulfide-based composite self-lubricating coating used in this embodiment for transmission shift forks includes the following steps: S1. First, prepare the binder (the mass ratio of silica sol, epoxy resin, phenolic resin, and vinyl resin is 1.0:1.0:1.0:1.0). Mix diatomaceous earth powder with the binder in a mass ratio of 1.0:2.0 to obtain a mixed slurry. S2. The mixed slurry is uniformly adhered to the surface of the transmission shift fork by immersion. The thickness of each application is 15μm. The coating is applied twice, and the immersion time is 12min per application. Then, it is dried and cured at 55℃ for 5h to obtain a transmission shift fork with diatomaceous earth attached. S3. Next, the molybdenum disulfide-based composite coating is placed in an ultrasonic cleaner to disperse it evenly. The ultrasonic temperature is 60°C and the ultrasonic time is 40 minutes to ensure uniform dispersion of the molybdenum disulfide-based composite coating. In this embodiment, the molybdenum disulfide-based composite coating consists of molybdenum disulfide, PEEK, and PFA, with a mass ratio of 1.0:0.5:0.6. After the molybdenum disulfide-based composite coating is evenly dispersed, it is once again applied to the transmission shift fork with diatomaceous earth attached by immersion. The coating thickness is 10 μm, and the immersion time is 18 minutes. After coating, it is dried and cured at 65°C for 6 hours. Finally, the surface is polished to obtain a molybdenum disulfide-based composite self-lubricating coating.
[0033] The molybdenum disulfide-based composite self-lubricating coating obtained in this embodiment was subjected to friction coefficient and wear rate tests using a liquid metal tribometer (LMT). The LMT was set with a load of 1 N, a frequency of 50 Hz, and a test time of 20 min. The friction and wear test curves are shown below. Figure 1 As shown, the initial friction coefficient of the molybdenum disulfide-based composite self-lubricating coating obtained in this embodiment is relatively high because the surface is relatively rough at the initial contact. As the surface gradually becomes smoother after running-in, the friction coefficient drops to a stable range (0.08~0.88) with small fluctuations, and the friction coefficient and wear rate are 0.083 and 1.21%, respectively.
[0034] Example 2 The difference from Example 1 is that in step S1, the mass ratio of diatomaceous earth powder to binder is 1.0:1.8; in step S3, the mass ratio of molybdenum disulfide, PEEK, and Ti3C2Tx powder in the molybdenum disulfide-based composite coating is 1.0:0.75:0.4.
[0035] The molybdenum disulfide-based composite self-lubricating coating obtained in this embodiment was subjected to friction coefficient and wear rate tests using a liquid metal tribometer (LMT). The LMT was set with a load of 1 N, a frequency of 50 Hz, and a test time of 20 min. The friction and wear test curves are shown below. Figure 2 As shown, the initial friction coefficient of the molybdenum disulfide-based composite self-lubricating coating obtained in this embodiment is relatively high because the surface is relatively rough at the initial contact. As the surface gradually becomes smooth after running-in, the friction coefficient drops to a stable range (0.105~0.115) with small fluctuations, and the friction coefficient and wear rate are 0.108 and 1.85%, respectively.
[0036] Example 3 The difference from Example 1 is that in step S1, the mass ratio of diatomaceous earth powder to binder is 1.0:2.8; in step S3, the mass ratio of molybdenum disulfide, black phosphorus powder, alumina powder, and titanium dioxide powder in the molybdenum disulfide-based composite coating is 1.0:0.25:0.7:0.3.
[0037] The molybdenum disulfide-based composite self-lubricating coating obtained in this embodiment was subjected to friction coefficient and wear rate tests using a liquid metal tribometer (LMT). The LMT was set with a load of 1 N, a frequency of 50 Hz, and a test time of 20 min. The friction and wear test curves are shown below. Figure 3 As shown, the initial friction coefficient rises rapidly because the surface is relatively rough at initial contact; as the surface gradually becomes smoother after running-in, the friction coefficient of the molybdenum disulfide-based composite self-lubricating coating obtained in this embodiment drops to a stable range (0.090~0.098), with small fluctuations, and the friction coefficient and wear rate are 0.095 and 1.59%, respectively.
[0038] Example 4 The difference from Example 1 is that in step S2, the drying and curing temperature is 65°C and the time is 7h; in step S3, the mass ratio of molybdenum disulfide, PEEK and PFA in the molybdenum disulfide-based composite coating is 1.0:0.5:0.6, and the drying and curing temperature is 75°C and the time is 7h.
[0039] The molybdenum disulfide-based composite self-lubricating coating obtained in this embodiment was subjected to friction coefficient and wear rate tests using a liquid metal tribometer (LMT). The LMT was set with a load of 1 N, a frequency of 50 Hz, and a test time of 20 min. The friction and wear test curves are shown below. Figure 4 As shown, the initial friction coefficient is relatively high because the surface is relatively rough at the initial contact. As the surface gradually becomes smoother after running-in, the friction coefficient of the molybdenum disulfide-based composite self-lubricating coating obtained in this embodiment drops to a stable range (0.105~0.115) with small fluctuations, and the friction coefficient and wear rate are 0.11 and 1.92%, respectively.
[0040] Example 5 The difference from Example 1 is that the immersion time in step S2 is 10 min; in step S3, the mass ratio of molybdenum disulfide, PEEK and PFA in the molybdenum disulfide-based composite coating is 1.0:0.5:0.6, and the immersion time is 15 min.
[0041] The molybdenum disulfide-based composite self-lubricating coating obtained in this embodiment was subjected to friction coefficient and wear rate tests using a liquid metal tribometer (LMT). The LMT was set with a load of 1 N, a frequency of 50 Hz, and a test time of 20 min. The friction and wear test curves are shown below. Figure 5 As shown, the initial friction coefficient rises rapidly because the surface is relatively rough at the initial contact. As the surface gradually becomes smoother after running-in, the friction coefficient of the molybdenum disulfide-based composite self-lubricating coating obtained in this embodiment stabilizes in the range of (0.240~0.253) with small fluctuations, and the friction coefficient and wear rate are 0.242 and 3.15%, respectively.
[0042] As can be seen from the experimental results of the above embodiments of the present invention, the coating obtained by the present invention has a friction coefficient ≤0.242 and a wear rate ≤3.15%, and has good wear resistance.
[0043] Comparative Example 1 The difference from Example 1 is that this comparative example only performed step S3 of Example 1, which involves uniformly coating the transmission fork with molybdenum disulfide composite coating.
[0044] The coating obtained in this comparative example was subjected to friction coefficient and wear rate tests using a liquid metal tribometer (LMT). The LMT was set with a load of 1 N, a frequency of 50 Hz, and a test time of 20 min. The tribometer test curves are shown below. Figure 6As shown, the initial coefficient of friction of the coating obtained in this comparative example increases rapidly due to the roughness of the surface during initial contact. As the surface gradually becomes smoother after break-in, the coefficient of friction stabilizes within the range of 0.340–0.355, with minimal fluctuation. The porous framework intermediate layer obtained by mixing diatomaceous earth powder and binder optimizes and improves the coating's adhesion, lubricant distribution, and other properties. The absence of this intermediate layer leads to reduced coating performance and a higher coefficient of friction, resulting in a coefficient of friction of 0.348 and a wear rate of 5.82%.
[0045] Comparative Example 2 The difference from Example 2 is that the mass ratio of diatomaceous earth powder to binder in step S1 is 2.0:1.3.
[0046] The coating obtained in this comparative example was subjected to friction coefficient and wear rate tests using a liquid metal tribometer (LMT). The LMT was set with a load of 1 N, a frequency of 50 Hz, and a test time of 20 min. The tribometer test curves are shown below. Figure 7 As shown, the initial coefficient of friction of the coating obtained in this comparative example increases rapidly due to the roughness of the surface during initial contact. As the surface gradually becomes smoother after break-in, the coefficient of friction decreases, eventually fluctuating within the range of 0.283 to 0.290. Excessive diatomaceous earth can lead to insufficient binder and a loose coating, resulting in a higher coefficient of friction. The obtained coefficient of friction and wear rate are 0.287 and 4.51%, respectively.
[0047] Comparative Example 3 The difference from Example 3 is that the mass ratio of diatomaceous earth powder to binder in step S1 is 1.0:4.5.
[0048] The coating obtained in this comparative example was subjected to friction coefficient and wear rate tests using a liquid metal tribometer (LMT). The LMT was set with a load of 1 N, a frequency of 50 Hz, and a test time of 20 min. The tribometer test curves are shown below. Figure 8 As shown, the initial friction coefficient of the coating obtained in this comparative example increases rapidly due to the relatively rough surface at initial contact. As the surface gradually becomes smoother after break-in, the friction coefficient stabilizes in the range of 0.290–0.310 with minimal fluctuation. Excessive binder may form an overly thick adhesive layer, affecting lubrication and resulting in a higher friction coefficient. The obtained friction coefficient and wear rate are 0.295 and 4.77%, respectively.
[0049] The experimental results from the comparative examples above show that the coating obtained has the lowest friction coefficient of 0.287, which is greater than the maximum value of 0.242 in the above embodiments of the present invention; and the lowest wear rate of 4.51%, which is greater than the maximum value of 3.15% in the above embodiments of the present invention, indicating good wear resistance. It is evident that the overall performance of the coating in the embodiments of the present invention is superior to that of the coating obtained in the comparative examples.
[0050] Based on the test data of the embodiments and comparative examples of this invention, it can be seen that the present invention can effectively improve performance by setting a porous diatomaceous earth intermediate layer and adopting a two-layer step-by-step dip-coating process. Specifically, Comparative Example 1, which only directly coats the molybdenum disulfide surface layer and lacks the diatomaceous earth intermediate layer, has a final friction coefficient of 0.348 and a wear rate of 5.82%, while Example 1, which has diatomaceous earth attached, has a friction coefficient of only 0.083 and a wear rate of 1.21%. The other preparation conditions of the two are completely the same, and the performance difference comes from the difference in interface structure: the surface of the metal fork substrate is dense and smooth, while the single-layer molybdenum disulfide coating relies only on resin adhesion. When two surfaces are bonded together, the mechanical and thermal properties of the substrate and the coating differ. During reciprocating friction, stress concentration easily occurs at the interface, and the coating is prone to peeling and flaking. In contrast, the porous intermediate layer formed by the mixture of diatomaceous earth and binder can conform to the micro-uneven structure of the substrate on the inner side and allow molybdenum disulfide coating to penetrate and fill on the outer side, forming a two-way mechanical interlocking and anchoring structure. This structurally improves the bonding strength of the coating. At the same time, the pores can store molybdenum disulfide lubricating particles, continuously supplying lubricating medium to the contact surface during friction and maintaining a stable lubricating film. Without the intermediate layer, the lubricating phase only adheres to the surface layer and will be completely consumed by friction in a short time, resulting in a rapid decline in lubrication effect.
[0051] The mixing ratio range of diatomaceous earth and binder 1.0: (1.0~3.0) has also been verified by gradient test. The deviation of the mixing ratio from the range will directly destroy the porous skeleton structure. In Comparative Example 2, where the proportion of diatomaceous earth was too high (mass ratio 2.0:1.3), the binder was insufficient to completely encapsulate the diatomaceous earth particles, resulting in loose bonding of the intermediate layer particles. During friction, the skeleton was easily pulverized and peeled off, the anchoring effect failed, and the friction coefficient increased to 0.287 with a wear rate of 4.51%. In Comparative Example 3, where the binder had an excessive ratio of 1:4.5, the excess resin blocked the internal pores of the diatomaceous earth, causing it to lose both mechanical interlocking points and the ability to store lubricating medium. The molybdenum disulfide only floated on the coating surface and was easily worn away during friction, resulting in a friction coefficient of 0.295 and a wear rate of 4.77%. Only within the ratio range specified in this invention (i.e., 1.0:(1.0~3.0)) can the binder just encapsulate the diatomaceous earth to form a complete skeleton while retaining interconnected pores, thus balancing the structural strength of the intermediate layer and its dual functions of oil storage and anchoring, achieving optimal coating friction and wear performance.
[0052] In summary, this invention introduces diatomaceous earth to construct a porous framework intermediate layer. Its porous microstructure forms a strong mechanical bond and anchoring effect with the substrate and the upper lubricating coating, improving interfacial bonding strength, alleviating stress mismatch between the coating and the substrate, and effectively solving the problems of weak adhesion and easy detachment when directly coating MoS2. Simultaneously, the porous framework can uniformly bear and disperse the MoS2 lubricating phase, preventing agglomeration, sedimentation, or uneven distribution of the lubricating phase, ensuring a stable supply of lubricating phase at the friction interface. This achieves a synergistic improvement in low friction coefficient and high wear resistance, meeting the coating requirements of self-lubricating coatings for the transmission forks of aircraft pneumatic-hydraulic actuators.
[0053] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.
Claims
1. A dip-coating method for a high-adhesion molybdenum disulfide-based composite self-lubricating coating for a transmission shift fork, characterized in that, The process includes the following: S1. Mix diatomaceous earth powder and binder evenly at a mass ratio of 1.0:(1.0~3.0) to obtain a mixed slurry; S2. Apply the mixed slurry evenly to the substrate surface using an impregnation method. The thickness of each application is 10-18 μm, and the coating is applied 1-3 times. Then, dry and cure the coating to obtain a substrate with diatomaceous earth attached. S3. The molybdenum disulfide-based composite coating is uniformly dispersed by ultrasonication, and then uniformly coated onto the substrate with diatomaceous earth by impregnation. The coating thickness is 8-15 μm. After coating, the coating is dried and cured, and finally polished to obtain a molybdenum disulfide-based composite self-lubricating coating.
2. The dip-coating method for a high-adhesion molybdenum disulfide-based composite self-lubricating coating for a transmission shift fork according to claim 1, characterized in that, The adhesive is at least one of silica sol, epoxy resin, phenolic resin, and vinyl resin.
3. The dip-coating method for a high-adhesion molybdenum disulfide-based composite self-lubricating coating for a transmission shift fork according to claim 1, characterized in that, In step S2, the drying and curing temperature is 30-70℃, and the drying and curing time is 2-8 hours.
4. The dip-coating method for a high-adhesion molybdenum disulfide-based composite self-lubricating coating for a transmission shift fork according to claim 1, characterized in that, In step S3, the molybdenum disulfide-based composite coating is ultrasonically dispersed until it reaches a non-Newtonian high-viscosity fluid state.
5. A dip-coating method for a high-adhesion molybdenum disulfide-based composite self-lubricating coating for a transmission shift fork according to claim 1 or 4, characterized in that, In step S3, the ultrasonic temperature is 35–70°C and the ultrasonic time is 15–110 min.
6. The dip-coating method for a high-adhesion molybdenum disulfide-based composite self-lubricating coating for a transmission shift fork according to claim 1, characterized in that, In step S3, the drying and curing temperature is 45-80℃, and the drying and curing time is 3-10h.
7. The dip-coating method for a high-adhesion molybdenum disulfide-based composite self-lubricating coating for a transmission shift fork according to claim 1, characterized in that: The components of the molybdenum disulfide-based composite coating include: molybdenum disulfide, PEEK, and Ti3C2Tx powder; wherein the mass ratio of molybdenum disulfide, PEEK, and Ti3C2Tx powder is 1.0:(0.5-1.2):(0.1-0.6). Alternatively, the components of the molybdenum disulfide-based composite coating include: molybdenum disulfide, PEEK, and PFA; wherein the mass ratio of molybdenum disulfide, PEEK, and PFA is 1.0:(0.3-1.0):(0.2-1.2). Alternatively, the components of the molybdenum disulfide-based composite coating include: molybdenum disulfide, black phosphorus powder, alumina powder, and titanium dioxide powder; wherein the mass ratio of molybdenum disulfide, black phosphorus powder, alumina powder, and titanium dioxide powder is 1.0:(0.1-0.4):(0.1-0.8):(0.1-0.5).
8. The dip-coating method for a high-adhesion molybdenum disulfide-based composite self-lubricating coating for a transmission shift fork according to claim 1, characterized in that, In step S2, the immersion time for a single immersion is 10 to 15 minutes; in step S3, the immersion time is 15 to 20 minutes.
9. A high-adhesion molybdenum disulfide-based composite self-lubricating coating for a transmission shift fork, characterized in that, The coating was prepared by dip coating method according to any one of claims 1-8 for a high-bonding molybdenum disulfide-based composite self-lubricating coating for a transmission shift fork.
10. A high-adhesion molybdenum disulfide-based composite self-lubricating coating for a transmission shift fork according to claim 9, characterized in that, The high-adhesion molybdenum disulfide-based composite self-lubricating coating used for the transmission shift fork exhibits a friction coefficient ≤0.242 and a wear rate ≤3.15% under the following conditions: load 0.95-1.05N, frequency 45-50Hz, and test time 18-22min.